Prevalence, Contamination Level, and Associated Factors of Methicillin-Resistant Staphylococcus aureus in Raw Cow Milk at Selected Districts of Gamo Zone, Southern Ethiopia - Edget Abayneh Alembo; Tomas Tonjo Torka (Veterinary Medicine International)
Staphylococcus aureus is pathogenic bacterium contaminating milk and milk products causing bacterial food poisoning. In the current study sites, there is no information on methicillin-resistant Staphylococcus aureus. Thus, the current study sought to assess the risk factors that contribute to the contamination of raw cow milk, the bacterial load, and the prevalence of methicillin-resistant Staphylococcus aurous. A cross-sectional study was conducted, January to December, 2021, on randomly selected 140 milk samples from selling point of Arba Minch Zuria and Chencha districts. Fresh milk samples were processed and tested for bacterial load, bacterial isolation, and methicillin susceptibility patterns. Questionnaire survey was conducted on 140 producers and collectors to assess hygienic factors attributed to contamination of raw cow milk with Staphylococcus aureus. The overall prevalence of S. aureus was 42.1% (59/140) (95% confidence interval (CI): 34.80–51.40%). About 15.6% (22/140) of the milk samples assessed had the viable count and total S. aureus count higher than 5log cfu/mL with 5.3 + 1.68 and 1.36 + 1.7log cfu/ml−1 bacterial loads, respectively. The rate of isolation of S. aureus was significantly high in milk from highland than lowland (p=0.030). The multivariable logistic regression revealed that educational status (OR: 6.00; 95% CI: 4.01–8.07), picking one’s nose while working on milk (OR: 1.41; 95% CI: 0.54–2.25), cleaning the milk can (OR: 4.5; 95% CI: 2.61–5.17), hand washing activities (OR: 3.4; 95% CI: 1.670–6.987), check for abnormal milk (OR: 2; 95% CI: 1.55–2.75), and container for milk (OR: 3; 95% CI: 0.12–0.67) were risk factors significantly associated with the occurrence of S. aureus in milk. In conclusion, the highest rate of resistance was observed to ampicillin (84.7%) and cefoxitin (76.3%). All isolates are resistant to at least two types of antimicrobial drugs, while 65.0% of the isolates were found to be multidrug-resistant. The higher prevalence, high load, and antimicrobial resistance of S. aureus indicate the higher public health risk due to the widespread consumption of raw milk in the area. Furthermore, consumers in the study area should be aware of the risks associated with consuming raw milk.